Left atrial appendage mass: is it always a thrombus? - Sahratov, Hikmet; Guler, Adem; Kurkluoglu, Mustafa; Yesil, Fahri Gurkan; Tavlasoglu, Murat; Cingoz, Faruk (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Myxomas are the most common benign tumors of the heart. Cardiac myxomas are found in the left atrium in 80–90% of cases and are often attached to the interatrial septum. Myxomas originating from the left atrial appendage are very rare. In this report, we present a patient in whom surgery was performed after the diagnosis of mitral valve stenosis, chronic atrial fibrillation, and a possible left atrial appendage (LAA) thrombus (which was incidentally diagnosed as a myxoma).